2020
DOI: 10.3390/cancers12082212
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Intraperitoneal Chemotherapy in Patients with Pseudomyxoma Peritonei—A Novel Treatment Approach

Abstract: Neoadjuvant intravenous chemotherapy in patients with pseudomyxoma peritonei (PMP) has not shown convincing results. The effectiveness of neoadjuvant intraperitoneal (IP) chemotherapy has never been reported. This prospective, non-randomized phase II study included patients with PMP treated between May 2017 and December 2018, who were not considered suitable for primary cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC). The majority of patients were treated with laparoscopic HIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…The application of preoperative intraperitoneal chemotherapy in PMP has only been reported in some case reports and small sample studies, which showed a good result [12][13]. Strati ed analysis in this study shows that preoperative intraperitoneal chemotherapy tends to prolong survival.…”
Section: Natural Course Of Pmpmentioning
confidence: 56%
“…The application of preoperative intraperitoneal chemotherapy in PMP has only been reported in some case reports and small sample studies, which showed a good result [12][13]. Strati ed analysis in this study shows that preoperative intraperitoneal chemotherapy tends to prolong survival.…”
Section: Natural Course Of Pmpmentioning
confidence: 56%
“…The potential role of neoadjuvant intraperitoneal chemotherapy was already emphasized in other appendiceal entities (pseudomyxoma) [ 38 ]. The probable effectiveness of other types of intraperitoneal administrations in the context of peritoneal disease of appendiceal origin adds to the rationale of PIPAC, in spite of the clinical setting of the present study that is limited to appendiceal adenocarcinoma [ 12 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment course was repeated every 3 weeks for 3 courses. 14 Four to 6 weeks after the last cycle of preoperative chemotherapy, patients received r-CRS combined with upper-abdominal partial peritonectomy or l-CRS combined with upper-abdominal partial peritonectomy. The inclusion criteria were (1) patients diagnosed as having PMP with limited peritoneal surface malignancy (PSM) that was confined to the upper-abdominal parietal peritoneum (PCI <10) and some implants in the omentum by staging laparoscopy performed preliminarily; and (2) absence of a huge intra-abdominal mass that was difficult to handle by robotic approach.…”
Section: Methodsmentioning
confidence: 99%